Correlation between follicle diameter and pre-ovulatory metabolic profile in Bos grunniens - Yan, Jiuru; Fu, Yuxin; Lan, Lan; Zhang, Huizhu; Huang, Ling; Wang, Yaying; Xiong, Xianrong; Yin, Shi; Li, Jian; He, Honghong (Frontiers in Veterinary Science, 2025)
IntroductionIn this study, we investigated the metabolic profiles of yak (Bos grunniens) follicles during the development period from the perspective of metabolomics, aiming to screen out the differential metabolites of yak follicles in different sizes and potential pathways during yak follicle development and to provide a basis for the study of follicle development and developmental mechanisms in the further stage of development.MethodsA total of 20 four-year-old female yaks were selected, and follicles of different sizes were collected after slaughter and divided into d < 3 mm, 3–6 mm and d > 6 mm. The follicular fluid was collected, 6 replicates per group and subjected to LC–MS assay, combined with multidimensional and unidimensional statistical analyses to screen the differential metabolites between follicles of different sizes. Differential metabolites enriched KEGG pathways to screen the pathways that might be related to follicle development.ResultsWe found that most of the metabolites were mainly enriched in amino acid metabolism pathways, energy metabolism pathways and other pathways of cofactor synthesis, and that during the development of the small follicle to the large follicle, 2-Lysophosphatidylcholine, PC (17:0/0:0), PC (16:0/0:0), and LysoPC (18:0/0:0) were down-regulated; Dioctyl succinate, P-Coumaraldehyde, ISOPRENE, L-Isoleucine, Dioctyl succinate up-regulated.ConclusionThese results suggest that amino acid metabolism, the production of steroid hormones and their metabolites, and the metabolic activity of granulosa cells play important roles in follicle development. The results provide a theoretical basis for further exploration of follicular development in yak.